Molecular etiological profile of atypical bacterial pathogens, viruses and coinfections among infants and children with community acquired pneumonia admitted to a national hospital in Lima, Peru - del Valle-Mendoza, Juana (2017)
Objective: The main objective of this study was to detect the presence of 14 respiratory viruses and atypical bacteria (Mycoplasma pneumoniae, Chlamydia pneumoniae), via polymerase chain reaction in patients under 18 years old hospitalized due to community-acquired pneumonia (CAP) from Lima, Peru. Results: Atypical pathogens were detected in 40% (58/146); viral etiologies in 36% (52/146) and coinfections in 19% (27/146). The most common etiological agent was M. pneumoniae (n = 47), followed by C. pneumoniae (n = 11). The most frequent respiratory viruses detected were: respiratory syncytial virus A (n = 35), influenza virus C (n = 21) and parainfluenza virus (n = 10). Viral-bacterial and bacterium-bacterium coinfections were found in 27 cases. In our study population, atypical bacteria (40%) were detected as frequently as respiratory viruses (36%). The presence of M. pneumoniae and C. pneumoniae should not be underestimated as they can be commonly isolated in Peruvian children with CAP.